2014
DOI: 10.1182/blood.v124.21.3617.3617
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact and Targeting of BMI-1 in Acute Myeloid Leukemia

Abstract: A minor fraction of leukemia cells, leukemia stem cells, have been shown to be highly resistant to current therapies and thought to be responsible for recurrence. BMI-1, a part of polycomb repressive complex 1 (PRC1) is essential for the self-renewal of normal hematopoietic and leukemia stem cells. PTC-209 is a novel selective transcriptional inhibitor of BMI-1, which has been shown to have antitumor activity against cancer-initiating cells in colorectal cancer. We investigated the prognostic significance of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…77 Another independent study published in the 56th American Society of Hematology conference reported prognostic value of BMI1 expression in 511 newly diagnosed AML patients. 78 This study suggests that BMI1 expression was higher in AML with unfavorable cytogenetics ( n = 252) compared to intermediate ( n = 225) or favorable cytogenetics ( n = 34). Higher BMI1 levels were associated with shorter median overall survival (OS).…”
Section: Bmi1 and Myeloid Malignanciesmentioning
confidence: 69%
“…77 Another independent study published in the 56th American Society of Hematology conference reported prognostic value of BMI1 expression in 511 newly diagnosed AML patients. 78 This study suggests that BMI1 expression was higher in AML with unfavorable cytogenetics ( n = 252) compared to intermediate ( n = 225) or favorable cytogenetics ( n = 34). Higher BMI1 levels were associated with shorter median overall survival (OS).…”
Section: Bmi1 and Myeloid Malignanciesmentioning
confidence: 69%
“…PTC‐209 also shows more critical cytotoxic effects in acute myeloid leukemia (AML) than in ALL cells. Treatment with PTC‐209 causes BAX conformational change, activates caspase‐3 and DNA fragmentation, decreases mitochondrial membrane potential (MMP), and externalizes phosphatidylserine (PS) . PTC596 (PTC Therapeutics), an orally bioavailable selective SMI1 inhibitor, modifies BMI1 posttranslation, degrades BMI1 protein, and reduces PRC1 activity in glioblastoma, fibrosarcoma, and leukemia.…”
Section: Targeting Pcg Proteins For Cancer Prevention and Therapymentioning
confidence: 99%